Presence of Periodontopathic Bacteria DNA in Atheromatous Plaques from Coronary and Carotid Arteries - Szulc, Malgorzata (Biomed Res Int, 2015)
Objectives. Interest in periodontitis as a potential risk factor for atherosclerosis and its complications resulted from the fact that the global prevalence of periodontal diseases is significant and periodontitis may induce a chronic inflammatory response. Many studies have analyzed the potential impact of the Porphyromonas gingivalis, major pathogen of periodontitis, on general health. The purpose of this study was to find the presence of the Porphyromonas gingivalis DNA in the atherosclerotic plaques of coronary and carotid arteries and in the periodontal pockets in patients with chronic periodontitis, who underwent surgery because of vascular diseases. Methods and Results. The study population consisted of 91 patients with coronary artery disease or scheduled for carotid endarterectomy. The presence of Porphyromonas gingivalis DNA in atheromatous plaques and in subgingival samples was determined by PCR. Bacterial DNA was found in 21 of 91 (23%) samples taken from vessels and in 47 of 63 (74.6%) samples from periodontal pockets. Conclusions. Porphyromonas gingivalis DNA is frequently found in atheromatous plaques of patients with periodontitis. That is why more research should be conducted to prove if this periopathogen may have an impact on endothelium of patients at risk of atherosclerosis.